ANALISIS KINERJA DINAS PEKERJAAN UMUM PENATAAN RUANG DAN PERUMAHAN RAKYAT BIDANG BINA MARGA DALAM PEMBANGUNAN JALAN DI PROVINSI KALIMANTAN TIMUR - Anastasia Rizki Nilakandi Bachri (ADMINISTRASI PUBLIK, 2020)
The study entitled "Performance Analysis of the Public Works Office of Spatial Planning and Public Housing in Bina Marga in Road Development in East Kalimantan Province" raises the problem formulation of how the performance of the Public Works Office of Spatial Planning and Public Housing in Bina Marga in carrying out road construction in Kalimantan Province East. This research was conducted with the aim of finding out the performance of the Public Works Agency for Spatial Planning and Public Housing in Bina Marga in carrying out road construction in East Kalimantan Province. This research itself is a qualitative descriptive study. The focus of this research is the Quality, Responsiveness and Accountability of the Public Works Department of Spatial Planning and Public            Based on the results of the study, the Performance of the Public Works Office of Spatial Planning and Public Housing in the Highways Sector is quite good. based on the road construction work carried out by the Public Works Office of Spatial Planning and Public Housing in the Highways Sector, it can be seen that it has been done to the maximum. However, there is still road construction work which is considered to be still not optimal.